If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3d-13=13
We move all terms to the left:
3d-13-(13)=0
We add all the numbers together, and all the variables
3d-26=0
We move all terms containing d to the left, all other terms to the right
3d=26
d=26/3
d=8+2/3
| 4z+6=2z+10* | | 3x-12-12=243 | | 2x-7=-x+45 | | -9=33x-244 | | r2+5r-66=0 | | 7b–2–12b=63 | | -11+2(2x+7)=4x+10 | | 5^x=163 | | –9d=10−8d | | 3•m=51 | | 4(2x-2)=52 | | 4x-8+5x+x=180 | | 2+5t=7t+10 | | 72=8c | | 10−5x=0 | | 8(6+4x)=-92 | | x+1-6x=-5(x-1)+4 | | 15-3=12x3 | | 5z+3=38 | | a-6;a=-3 | | -3x-3=3(-x-13) | | 3x+4=3(x+1)=1 | | 3(m+2=1/4(12m+24) | | 3x+12+12=243 | | 15x+(-10)=-6 | | 4x-12=2(2x-18) | | 3y–8y=25 | | 5-3x=38 x= | | 5(x-6)=10-4(x-8) | | 27−=2w | | 3x+25=x-15 | | n+4÷15=1 |